Effects of prohibition and decriminalization on drug market conflict - Scott, Jacques (Criminology & public policy, 2016)
To reduce individual and social harms, most nations prohibit certain psychoactive drugs. Yet, prior scholarship has suggested that prohibition reduces illicit drug sellers’ access to law and thereby increases predation against and retaliation by them. No prior study, however, has directly tested that theory by comparing drug sellers of different legal statuses operating in a single place and time. This study analyzes rates of victimization, legal mobilization, and violent retaliation in three retail drug markets in Amsterdam, the Netherlands: the legally regulated alcohol trade of cafés, the decriminalized cannabis market of “coffeeshops,” and the illegal street drug market. Results from interviews conducted with 50 sellers in each market indicate, as expected, that illicit drug dealers have the highest rates of victimization and violent retaliation and the lowest rates of legal mobilization. Contrary to expectations, we find coffeeshops experience less victimization than cafés and have similar rates of violent retaliation and legal mobilization.